2004
DOI: 10.4049/jimmunol.172.11.7154
|View full text |Cite
|
Sign up to set email alerts
|

Topical Glucocorticoid Therapy Directly Induces Up-Regulation of Functional CXCR4 on Primed T Lymphocytes in the Aqueous Humor of Patients with Uveitis

Abstract: Overexpression of the constitutive chemokine receptor CXCR4 has been shown to contribute to the accumulation of leukocytes at sites of chronic inflammation. Glucocorticoids are widely used to treat inflammatory disorders such as uveitis to considerable effect, yet paradoxically have been reported to increase CXCR4 expression in vitro. We show here that ocular lymphocytes isolated from patients with uveitis who had been treated with topical glucocorticoids expressed highly elevated levels of CXCR4. The up-regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
17
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 57 publications
4
17
0
Order By: Relevance
“…14 In addition, SDF-1/CXCR4 potentially mediates ocular inflammation by recruiting CD4 ϩ T-cells, and is potentially involved in the formation of proliferative membranes in eyes with proliferative vitreoretinopathy. 15,16 Therefore, interest in understanding the role of SDF-1/CXCR4 in non-neovascular inflammatory or proliferative ocular diseases remains great.…”
mentioning
confidence: 99%
“…14 In addition, SDF-1/CXCR4 potentially mediates ocular inflammation by recruiting CD4 ϩ T-cells, and is potentially involved in the formation of proliferative membranes in eyes with proliferative vitreoretinopathy. 15,16 Therefore, interest in understanding the role of SDF-1/CXCR4 in non-neovascular inflammatory or proliferative ocular diseases remains great.…”
mentioning
confidence: 99%
“…13,14,33 There have been several reports demonstrating that GCs and DM can directly up-regulate CXCR4 expression in monocytes and T lymphocytes, resulting in an increased capacity of these cells to migrate in response to CXCL12. 13,14,33 However, in those published studies, GC treatment required more extensive incubation times (up to 16 hours) before any effects on CXCR4 expression could be observed. In contrast, our DM effects on cell migration were observed as early as 5 minutes after DM treatment, with optimal effects on migration being noted at the 2-hour time interval, which failed to demonstrate any change in CXCR4 cell surface expression on primary human T cells or Jurkat cells ( Figure S5A).…”
mentioning
confidence: 99%
“…Recent studies showed that this chemokine axis is also involved in several inflammatory diseases, including rheumatoid arthritis (Nanki et al, 2000;Tamamura et al, 2004;Haas et al, 2005), inflammatory liver diseases (Terada et al, 2003;Wald et al, 2004), uveitis (Curnow et al, 2004), and pulmonary fibrosis (Phillips et al, 2004). Nanki et al (2000) reported that memory T cells highly express CXCR4, and the CXCL12 concentration is extremely high in the synovial fluid of patients with rheumatoid arthritis.…”
mentioning
confidence: 99%